Organisation of instep kicking in young U11 to U20 soccer players. Issue 2 (3rd April 2021) - Palucci Vieira, Luiz H.; Barbieri, Fabio A.; Kellis, Eleftherios; Oliveira, Lucas; Aquino, Rodrigo; Cunha, Sérgio; Bedo, Bruno; Manechini, João; Santiago, Paulo
ABSTRACT: Aim: The main purpose of the study was to investigate kicking kinematics and performance in young-trained soccer players according to age, playing status, and biological maturity.Methods: Youth male soccer players ( N = 105) from five age groups (under-11, under-13, under-15, under-17, and under-20) were evaluated. Four digital video cameras (300 Hz) captured the participants' lower extremity and ball kinematics during penalty kick trials using dominant limb.Results: It was possible to identify non-linear differences in angular joint kinematics (displacement and velocity) of hip, knee and ankle across age-groups. Kicked ball speed and lower extremity mechanical factors discriminated among under-15 players with distinct status (e.g., ball speed and foot-to-ball speed ratio: starters > non-starters and non-participating substitutes; effect size = 1.05 to 1.49 [ large ]). Estimated maturity offset was not correlated with performance outputs in any age-group (r = −0.28 to 0.39; P > 0.05).Conclusion: We conclude that from ages 10 to 19 years, differences in kicking kinematics and performance vary across time in youth players. Transition phase between under-13 to under-15 appears the most sensible period for powerful instep kick performance development. Kicking speed in youth soccer is discriminated according to player status, but not estimated biological maturity.